The Effect of Earnings per Share and Debt to Equity Ratio On Audit Delay - Firli Agusetiawan Shavab; Deti Susilawati; Evi Dora Sembiring; Fuadi Fuadi (Journal of Applied Business, Taxation and Economics Research, 2023)
This study was conducted to determine the effect of Earning Per Share and DebtTo Equity Ratio on Audit Delay in property companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling method uses Purposive Sampling with a quantitative approach. The data analysis methods carried out include: (1) Descriptive statistics, (2) Testing classical assumptions, (3) Multiple linear regression analysis. (4) Double correlation test (5) Coefficient of Determination. (6) Test the Hypothesis (t-test and F-test).Based on the partial test results, it shows that earnings per share have an effect on Audit Delay, and debt to quity ratio has no effect on Audit Delay in Real Estate and Property Sector Companies Listed on the Indonesia Stock Exchange in 2017-2021. In simultaneous testing, earnings per share and debt to quity ratio together affect Audit Delay in Real Estate and Property Sector Companies Listed on the Indonesia Stock Exchange in 2017-2021. The percentage contribution of the effect of earnings per share and debt to quity ratio on Audit Delay is 17.7%, while the remaining 82.3% can be explained by other factors not examined in this study